(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The rapid expansion of scientific knowledge, technological progress and the complexity of modern life require educational systems to employ methodologies that promote holistic, interdisciplinary and practice-oriented learning. This article examines the integrative approach to teaching natural sciences in primary school, emphasizing its methodological, psychological and pedagogical foundations. The research demonstrates how integrative teaching stimulates curiosity, enhances practical and critical thinking, strengthens problem-solving skills and helps young learners connect scientific knowledge with daily experiences. The study also provides an in-depth analysis of theoretical frameworks, instructional models, classroom strategies and assessment approaches that align with contemporary educational standards. Findings show that integrative education enriches conceptual understanding, increases motivation and supports the formation of essential 21st-century competencies.